Inclusive early childhood education: exploring co-creation and the process of empowerment within participatory research and practice - Kate Carr-Fanning; Tanya Rihtman (Frontiers in Education)
IntroductionInclusive education and participatory research (PR) are both premised upon engaging with local unique needs, social justice, and empowerment. PR is limited through the lack of empirical exploration into the research approach itself, particularly its use in inclusive education. This paper explores findings from the co-construction process within a PR research project, which co-constructed a programme of inclusion for children with ADHD-type behaviours in kindergartens in countries in eastern/central Europe with local stakeholders.MethodsThis paper will draw on findings from methods used at particular phases of the project, including two researcher constructed questionnaires: a pre-post teacher training questionnaire and an open-ended qualitative survey of participants on the process of empowerment within co-creation. The qualitative data was subject to Thematic Analysis and the Wilcoxon Signed Ranks tests was used to analyse the results from the pre-post teacher training questionnaire.ResultsFindings support the use of participatory practices within inclusive education, especially teacher training, and the need for culturally and contextually relevant responses to including children with ADHD-type behaviours in early childhood education. Findings also emphasise particular experiences within and external to, but as a result of, the co-creation process, which were empowering, including collaborative dialogue, positioning within ones community, and finally the role of insider experts, and the emotional experience of being identified as an expert. Partners need to embrace this expert role, but they may be uncomfortable with or reject it.